Analysis Of Service Quality On The Surabaya Single Window (SSW) Website Using Modification E-Govqual Method - Zidan Catur Pamungkas; Muhammad Andik Izzudin; Andhy Permadi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The online licensing service provided by the Surabaya City Government is called the Surabaya Single Window (SSW). The positive effect of online licensing is the efficiency and effectiveness of bureaucrats' performance. In order to improve the quality of services for the citizens of Surabaya through E-government, it is necessary to provide feedback to the Surabaya City Government by analyzing the service quality of the Surabaya Single Window (SSW) website on user satisfaction. This research was conducted because the Surabaya City Government publishes no feedback regarding the quality of services available on the website. The website is the simplest benchmark in seeing the implementation of E-government, so the public and the Surabaya City Government need to know the quality of the website's services to the public. User satisfaction. This study aimed to determine how service quality affects user satisfaction on the Surabaya Single Window (SSW) website. The sample in this study was 99 respondents, calculated by the Slovin formula using the purposive sampling technique. The modified E-govqual method used in this study is because there are two additional variables, namely the visual quality variable and the overall variable, which are expected to help the service quality of the Surabaya Single Window (SSW) website. This study uses quantitative techniques with validity, reliability, classical assumptions, multiple linear regression analysis, T-test, and F test. Based on the results of this study, the service quality of the Surabaya Single Window (SSW) website has an effect of 77.9% on user satisfaction and has a correlation coefficient of 88.3%. It is concluded that the Surabaya Single Window (SSW) website has a positive correlation between user satisfaction and the quality of E-government services. The results of this study can be used as an evaluation for Surabaya Single Window (SSW) website developers and can be a reference for future research.